2018
DOI: 10.3389/fimmu.2018.01739
|View full text |Cite
|
Sign up to set email alerts
|

Combining Immune Checkpoint Inhibitors With Conventional Cancer Therapy

Abstract: Immune checkpoint inhibitors (ICIs) have recently revolutionized cancer treatment, providing unprecedented clinical benefits. However, primary or acquired therapy resistance can affect up to two-thirds of patients receiving ICIs, underscoring the urgency to elucidate the mechanisms of treatment resistance and to design more effective therapeutic strategies. Conventional cancer treatments, including cytotoxic chemotherapy, radiation therapy, and targeted therapy, have immunomodulatory effects in addition to dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
154
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(155 citation statements)
references
References 119 publications
1
154
0
Order By: Relevance
“…In conclusion, this study discloses some of the functional pathways of TIM-3 + TILs, which could improve their targeting in more specific therapeutic approaches in CRC patients.Vaccines 2020, 8, 71 2 of 17 checkpoints (IC) in suppression of anti-tumor immune responses to various malignancies provided new targets for immunotherapy. Despite the clinical efficacy of current available immunotherapies in cancer patients, a large proportion of CRC patients fail to respond mainly due to immune-cell mediated resistance [2].T-cell immunoglobulin and mucin domain containing 3 (TIM-3) is a member of mucin domain transmembrane protein family, which was initially recognized on CD4 + T helper 1 (Th1) and CD8 + T cytotoxic (Tc1) cells [3,4]. Later studies revealed that TIM-3 can also be expressed on other immune subsets, including T regulatory cells (Tregs) [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, this study discloses some of the functional pathways of TIM-3 + TILs, which could improve their targeting in more specific therapeutic approaches in CRC patients.Vaccines 2020, 8, 71 2 of 17 checkpoints (IC) in suppression of anti-tumor immune responses to various malignancies provided new targets for immunotherapy. Despite the clinical efficacy of current available immunotherapies in cancer patients, a large proportion of CRC patients fail to respond mainly due to immune-cell mediated resistance [2].T-cell immunoglobulin and mucin domain containing 3 (TIM-3) is a member of mucin domain transmembrane protein family, which was initially recognized on CD4 + T helper 1 (Th1) and CD8 + T cytotoxic (Tc1) cells [3,4]. Later studies revealed that TIM-3 can also be expressed on other immune subsets, including T regulatory cells (Tregs) [5].…”
mentioning
confidence: 99%
“…Vaccines 2020, 8, 71 2 of 17 checkpoints (IC) in suppression of anti-tumor immune responses to various malignancies provided new targets for immunotherapy. Despite the clinical efficacy of current available immunotherapies in cancer patients, a large proportion of CRC patients fail to respond mainly due to immune-cell mediated resistance [2].…”
mentioning
confidence: 99%
“…Previous investigators studied other combinations of conventional cytotoxic drugs and immunotherapies to achieve enhanced effects and overcome tumor resistance to classical chemotherapy (Yan et al, 2018). Since cytotoxic drugs may be either immunostimulatory or immunosuppressive (Nowak et al, 2006), it is important to find synergistic combinations and recognize antagonistic combinations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7,9–11 ] As such, the potential for immunotherapy to synergize with traditional treatments has been proposed and clinically verified in multiple therapeutic settings. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%